E-Worksheet of Problem Based Learning (PBL) Model on Physics Materials to Improve Critical Thinking Ability - Ahmad Muwafiq Abdillah (Synergy Education Journal of Multidisciplinary Language and Social Sciences, 2026)
Developing students' critical thinking skills has become an urgent priority in science education, yet conventional physics instruction often provides limited opportunities for higher-order thinking. This study investigates the effectiveness of Problem-Based Learning (PBL)-based e-worksheets in enhancing students' critical thinking skills on the topics of progressive and stationary waves. A quasi-experimental pretest-posttest control group design was employed involving two Grade XI science classes at SMAN 20 Makassar, with Class XI MIPA 1 serving as the experimental group and Class XI MIPA 2 as the control group. Data were collected through product assessment worksheets and critical thinking tests, and analyzed using normality, homogeneity, and independent-samples t-tests. The results demonstrate that the PBL-based e-worksheets significantly improved students' critical thinking skills compared with conventional instruction. This study contributes empirical evidence supporting the integration of digital PBL learning materials into physics education to promote students' higher-order thinking and active learning.